Intercomparison of Observed and Modelled Sea-Surface Topographic Time-Series Near the New England Seamounts - Hallock, Z. R.; Teague, W. J.; Thompson, J. D. (1990)
Data from four arrays of inverted echo sounders equipped with pressure sensors and from a two-layer, primitive equation numerical model of the northwest Atlantic (including a prescribed Deep Western Boundary Current) are intercompared. Standard deviations of correlations between them, are examined as a function of horizontal position. Variances contained in three spectral bands (secular - longer than 150 days; mesoscale - 150-20 days; high-frequency - 20-2 days) are also examined. High correlations between above-thermocline and barotropic surface-height components are found in all arrays. Remarkable agreement between model and observations is found for the region east of the New England Seamount Chain, in both basic statistics and band-averaged spectra. West of the NESC, differences are noted in spectral results and are partially related to a more easterly longitude for the onset of large-amplitude Gulf Stream meanders in the Model. Keywords: Ocean currents/models; Seamounts North Atlantic Ocean; Height finding; Ocean surface/forecasting. Availability: Naval Oceanographic and Atmospheric Research Laboratory, Stennis Space Center, MS 39529-5004.